Neuroscience, Psychology and Conflict Management - Rafferty, Judith (Open textbook library., 2024)
This peer reviewed eBook introduces readers to foundational concepts in neuroscience, cognitive psychology, personality psychology and social psychology to help explain why conflict occurs, how it develops and how it may be managed and/or resolved.